Finite element analysis of composite materials - Barbero, Ever J. (CRC Press, 2008)
In this text for a course in advanced mechanics of composite materials, Barbero (mechanical and aerospace engineering, West Virginia University) explains the theoretical and practical knowledge needed to perform detailed analysis of composite materials using finite element analysis software. He covers all of the major aspects of advanced analysis, including three-dimensional effects, viscoelasticity, edge effects, elastic instability, damage, and delamination. He also outlines the solution of boundary value problems using commercial finite element analysis software. About 50 complete examples are included, demonstrating how to formulate and execute finite element analysis and how to interpret the results in engineering terms. Source code for each example is available for download online. The examples primarily use ANSYS, but some use MATLAB. The chapter on buckling uses BM13, available free on the book's web site. It is assumed that the reader is familiar with the basic mechanics of composites as covered in introductory level textbooks.